Nationalism : A Short History - Greenfeld, Liah (Book collections on Project MUSE., 2019)
"Nationalism, often the scourge, always the basis of modern world politics, is spreading. In a way, all nations are willed into being. But a simple declaration, such as Grouvelle's, is not enough. As historian Liah Greenfeld shows in her new book, a sense of nation--nationalism--is the product of the complex distillation of ideas and beliefs, and the struggles over them. Greenfeld takes the reader on an intellectual journey through the origins of the concept "nation" and how national consciousness has changed over the centuries. From its emergence in sixteenth century England, nationalism has been behind nearly every significant development in world affairs over succeeding centuries, including the American and French revolutions of the late eighteenth centuries and the authoritarian communism and fascism of the twentieth century. Now it has arrived as a mass phenomenon in China as well as gaining new life in the United States and much of Europe in the guise of populism"--